Association of playing cards/mahjong with all-cause mortality in older adults: a cohort study - Miao Dai; Wei Jie; Jianbang Shi; Weiyun Zhao; Jinbing Zou; Ying Li; Xiang Wang (BMC Geriatrics)
Abstract Background Engagement in leisure activities such as playing cards or mahjong has been linked to cognitive and physical benefits among older adults. However, the relationship between playing cards/mahjong and all-cause mortality remains unclear. This study aims to explore the association between playing cards/mahjong and all-cause mortality in a cohort of older Chinese adults. Methods We analyzed data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) collected between 2002 and 2018. A total of 29,254 participants aged 65 or older were included in the study. Participants were categorized based on their frequency of playing cards/mahjong: almost every day, at least once a week, at least once a month or sometimes, and never. Cox proportional hazards models were applied to assess the association between playing cards/mahjong and all-cause mortality. Interaction and sensitivity analyses were conducted to explore potential effect modifications and the robustness of the findings. Results During a mean follow-up of 4.6 years, 7,651 participants died. Compared to participants who never played cards/mahjong, those who played almost every day had a significantly lower risk of all-cause mortality (HR = 0.88; 95% CI, 0.82–0.95). Participants who played at least once a week (HR = 0.84; 95% CI, 0.78–0.91) similarly demonstrated reduced mortality. Participants who consistently played cards/mahjong at least once a week at both baseline and follow-up had a significantly lower all-cause mortality risk compared to never-players (HR = 0.67; 95% CI: 0.52–0.86). Interaction analysis revealed that the protective effect of playing cards/mahjong was more pronounced in participants aged 80 or older (P-interaction < 0.001). Sensitivity analyses confirmed the robustness of these associations. Conclusion Older adults who regularly play cards/mahjong have a lower risk of all-cause mortality, especially in the oldest groups. These leisure activities may promote longevity, but further research is needed to understand why.